PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTARDI BURSA EFEK INDONESIA TAHUN 2014 - KHOIRUN NISA' (Jurnal Manajerial, 2018)
This study aims to analyze the influence of good corporate governance on company performance. This study uses good corporate governance mechanism indicators consisting of: board of commissioners, board of directors, audit committee as independent variables, while company performance as the dependent variable. The population used in this study were 45 companies listed on the Indonesia Stock Exchange (IDX) in 2014 to get 44 samples. These samples were selected using purposive sampling method. The test is carried out using linear regression. The results of the study identified that the commissioners who were significant had no effect on company performance (CFROA). While the board of directors and singfinally audit committee affect the company's performance (CFROA).